2011
DOI: 10.1186/1477-7827-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ovulation in Xenopuswithout hCG injection: the effect of adding steroids into the aquatic environment

Abstract: BackgroundThe African clawed frog, Xenopus laevis, is widely used in studies of oogenesis, meiotic cell cycle and early embryonic development. However, in order to perform such studies, eggs are normally collected after the injection of hCG into the dorsal lymph sac of fully-grown female frogs following pre-injection of PMSF. Although this protocol is established and used as standard laboratory approach, there are some concerns over whether the injections could cause the transmission of deleterious microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Because the mechanisms controlling reproduction in vertebrates are highly conserved, there are a number of hormones, neuropeptides and commercially available drugs used therapeutically in other taxonomic groups that can also be used reliably in a number of amphibian species ( Table 1). Gonadotropin releasing hormone (GnRH) and Human chorionic gonadotropin (hCG) (or variations thereof, i.e., PMSG and eCG) 17,18 , either individually or in combination, have been used extensively in amphibian captive breeding programs including: the Southern Rocky Mountain boreal (Anaxyrus boreas boreas) 4,19,20 ; the toad, Dusky Gopher frog, Rana sevosa (Langhorne et al, unpublished) 7 ; the Gulf Coast Waterdog, Necturus beyeri 20 ; Wyoming toad, Anaxyrus baxteri 18 ; the bullfrog, Rana catesbiana 21 ; the American toad, Anaxyrus americanus 22 ; the grass frog, Lymnodyaster tasmaniensis 23 ; the Coqui, Eleutherodactylus coqui 24 ; the Xenopus, Xenopus laevis 25 ; the Gunther's toadlet, Pseduophryne guentheri 26 ; the Northern Leopard frog, Lithobates pipiens; the Argentinian Horned-frog, Ceratophrys ornate; the Cranwell's horned-frog, C. cranwelli; the American ground-frog, Odontophrynus americanus 27 ; and the fire salamander (Salamandra) 228 . Steroid hormones, like progesterone (P4), are less commonly reported but have demonstrated good efficacy in eliciting ovulation and oviposition in some species of anurans 16,18,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the mechanisms controlling reproduction in vertebrates are highly conserved, there are a number of hormones, neuropeptides and commercially available drugs used therapeutically in other taxonomic groups that can also be used reliably in a number of amphibian species ( Table 1). Gonadotropin releasing hormone (GnRH) and Human chorionic gonadotropin (hCG) (or variations thereof, i.e., PMSG and eCG) 17,18 , either individually or in combination, have been used extensively in amphibian captive breeding programs including: the Southern Rocky Mountain boreal (Anaxyrus boreas boreas) 4,19,20 ; the toad, Dusky Gopher frog, Rana sevosa (Langhorne et al, unpublished) 7 ; the Gulf Coast Waterdog, Necturus beyeri 20 ; Wyoming toad, Anaxyrus baxteri 18 ; the bullfrog, Rana catesbiana 21 ; the American toad, Anaxyrus americanus 22 ; the grass frog, Lymnodyaster tasmaniensis 23 ; the Coqui, Eleutherodactylus coqui 24 ; the Xenopus, Xenopus laevis 25 ; the Gunther's toadlet, Pseduophryne guentheri 26 ; the Northern Leopard frog, Lithobates pipiens; the Argentinian Horned-frog, Ceratophrys ornate; the Cranwell's horned-frog, C. cranwelli; the American ground-frog, Odontophrynus americanus 27 ; and the fire salamander (Salamandra) 228 . Steroid hormones, like progesterone (P4), are less commonly reported but have demonstrated good efficacy in eliciting ovulation and oviposition in some species of anurans 16,18,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the exposure effects of gestagens on reptiles have found evidence of reduced steroid hormone synthesis and yolk development in alligators (Austin, 1991) and altered sex ratios in red-eared slider turtles (Wibbels and Crews, 1995). Changes in gonadal structure, final maturation of eggs, metamorphosis, and reproductive behavior have also been observed in African clawed frogs (Hoffmann and Kloas, 2012;Kvarnryd et al, 2011;Lorenz et al, 2011;Ogawa et al, 2011). In several species of fish, gestagens decrease fecundity, increase ovarian apoptosis, and alter development of secondary sexual characteristics (Paulos et al, 2010;Runnalls et al, 2013;Svensson et al, 2013;Zeilinger et al, 2009;Zucchi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Yolk will provide nutritional reserves necessary for embryo development. More recently, E 2 was also shown to enhance progesterone-induced ovulation, possibly through a stimulatory effect on gonadotropin synthesis (Ogawa et al 2011). In addition to E 2 endocrine effects, E 2 may have autocrine and/or paracrine effects, as E 2 inhibits follicle-enclosed oocyte maturation through inhibition of maturation-inducing steroid (MIS) synthesizing enzymes in vitellogenic species such as Rana pipiens (Schuetz 1972, Spiegel et al 1978, Lin & Schuetz 1983 or Oncorhynchus mykiss ( Jalabert et al 1984).…”
Section: Introductionmentioning
confidence: 99%